MiRNA-149 as a Candidate for Facial Clefting and Neural Crest Cell Migration. (March 2022) - Stüssel, L.G.; Hollstein, R.; Laugsch, M.; Hochfeld, L.M.; Welzenbach, J.; Schröder, J.; Thieme, F.; Ishorst, N.; Romero, R. Olmos; Weinhold, L.; Hess, T.; Gehlen, J.; et al.
Nonsyndromic cleft lip with or without palate (nsCL/P) ranks among the most common human birth defects and has a multifactorial etiology. Human neural crest cells (hNCC) make a substantial contribution to the formation of facial bone and cartilage and are a key cell type in terms of nsCL/P etiology. Based on increasing evidence for the role of noncoding regulatory mechanisms in nsCL/P, we investigated the role of hNCC-expressed microRNAs (miRNA) in cleft development. First, we conducted a systematic analysis of miRNAs expressed in human-induced pluripotent stem cell–derived hNCC using Affymetrix microarrays on cell lines established from 4 unaffected donors. These analyses identified 152 candidate miRNAs. Based on the hypothesis that candidate miRNA loci harbor genetic variation associated with nsCL/P risk, the genomic locations of these candidates were cross-referenced with data from a previous genome-wide association study of nsCL/P. Associated variants were reanalyzed in independent nsCL/P study populations. Jointly, the results suggest that miR-149 is implicated in nsCL/P etiology. Second, functional follow-up included in vitro overexpression and inhibition of miR-149 in hNCC and subsequent analyses at the molecular and phenotypic level. Using 3′RNA-Seq, we identified 604 differentially expressed (DE) genes in hNCC overexpressing miR-149 compared with untreated cells. These included TLR4 and JUNB, which are established targets of miR-149, and NOG, BMP4, and PAX6, which are reported nsCL/P candidate genes. Pathway analyses revealed that DE genes were enriched in pathways including regulation of cartilage development and NCC differentiation. At the cellular level, distinct hNCC migration patterns were observed in response to miR-149 overexpression. Our data suggest that miR-149 is involved in the etiology of nsCL/P via its role in hNCC migration.